The Influence of Contingent Reasons on the Employ of Manifold Performance Measures in the Banking Industry: The Case of Libya - الفاخري جمعة (Dirasat in Economics and Business, 2017)
The purpose of this work is to explore the utilize of financial and non financial performance measures in the Libyan banking sector and to assess the influence of contingent factors on the use of financial and non financial performance measures from a contingency perspective. Thus, the research identifies the reality of performance measures taken from the performance measurement literature, and explores the effect of four selected contingent factors namely organizational structure, level of competition, size of bank, and business strategy of banks on the employ of performance measures. Based on a scale survey in a sample of 43 respondents from diverse banks in Libya, the research develops hypotheses concerning, its objectives, and uses descriptive analysis to assess the underlying impact of using financial and non financial performance measures. The impact of selected factors on the use of performance measures was also assessed by means of bivariate correlation statistics. The research results have revealed that most of the Libyan banks are still relying heavily on financial measures even if they tend to place strong emphasis on customers and quality dimensions of non financial measures. Moreover, The research has also found that all four contingent factors have varied positive impact on the use of performance measures in the Libyan banks.